Meningkatkan Hasil Belajar Matematika Siswa Melalui Guided Discovery Learning pada Materi Trigonometri di Kelas X - Sholikhah, Ummatus; Machmud, Tedy; Pauweni, Khardiyawan A. Y. (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2024)
This study aimed to determine the improvement of student’s mathematics learning outcomes by implementhing the Guided Discovery Learning learning model on trigonometric material in grade X of SMKS (Vocational High School) Salafiyah Syafi’iyah Randangan, academic year 2023/2024. The data in this study was collected through teacher activity observation sheet, student activity observation sheet (given to 20 student), and learning outcome test. The research indicators were: the results of observation of teacher activities in managing learning activities reached at least 75%, the result of observation of student activities in receiving learning activities reached the “Active” criterion with a minimum of 75%, the result of the assessment of mathematics learning outcomes were at least 75%, and all students reached the minimum completeness criterion (75). Based on the analysis, applying the Guided Discovery Learning learning model to trigonometric material could improve students’ mathematics learning outcomes in two cycles after learning improvements were made from cycles I to II. this was marked by the escalation result of 1) observation of teacher activities in managing learning (cycle I 55,98%, and cycle II 97,06%), 2) observation of student activities during the learning process (cycle I 40%, and cycle II 93,3%), and 3) yhe average of student mathematics learning outcome (12 student or 60% in cycle I, and 18 student or 90% students completed in cycle II).